O12.4. EFFECTS OF THE GLUCAGON-LIKE PEPTIDE-1 RECEPTOR AGONIST EXENATIDE ON BONE STATUS IN OBESE, NON-DIABETIC, ANTIPSYCHOTIC-TREATED SCHIZOPHRENIA SPECTRUM PATIENTS. (9th April 2019) - Eriksson, Robert; Broberg, Brian V; Ishoy, Pelle Lau; Bak, Nikolaj; Andersen, Ulrik B; Jørgensen, Niklas R; Knop, Filip K; Ebdrup, Bjorn
Abstract: Background: Low bone mineral density (BMD) may constitute an underestimated comorbidity in schizophrenia patients undergoing long-term antipsychotic treatment. Glucagon-like peptide 1 (GLP-1) receptor agonists are antidiabetic drugs, which may also affect bone turnover. The current study comprises planned secondary analyses of the 'TAO study': Treatment of antipsychotic-associated obesity with a GLP-1 receptor agonist. The TAO study was an investigator-initiated, double-blind, randomized, placebo-controlled trial, investigating the effects of three months treatment with the GLP-1 receptor agonist exenatide 2 mg once-weekly in chronic obese, antipsychotic-treated patients with schizophrenia spectrum disorder. Methods: First, we compared baseline bone turnover markers (BTMs) of 45 chronic, obese, antipsychotic-treated patients with the Danish Health2006 study cohort as reference population, and we calculated bone mineral density (BMD) T- and Z-scores. Second, investigated effects of three months of GLP-1 receptor agonist exenatide 2 mg once-weekly (n=23), or placebo (n=22) on BTMs and BMD in these patients. Data were initially analyzed without covariates by two-way repeated measures ANOVA. All analyses were repeated with mean prolactin level as a covariate to evaluate the potential effect of prolactin. Results: In women (n=24), all baseline BTM measurements of procollagen type I N-terminal propeptide (PINP) and C-terminal cross-linking telopeptide of type I collagen (CTX) were within reference values. In men (n=21), 5% displayed lower PINP and 14% displayed lower CTX. One patient displayed BMD Z-score <-2, and 23% of patients (17% of women and 29% of men) displayed -2.5<T-scores<-1 indicating osteopenia, but none had osteoporosis. After exenatide treatment, PINP decreased at trend level significance (P=0.05), and BMD increased for L2–L4 (P=0.016). No changes in bone markers were significant after correction for mean prolactin levels. Discussion: Sex- and age-adjusted measures of bone status in chronic, obese, antipsychotic-treated patients appeared comparable to the reference population. Subtle changes in bone markers during three-month exenatide treatment may suggest beneficial effects of GLP-1 receptor agonists on bone status in antipsychotic-treated patients, and further studies should consider the potential influence of prolactin.